2011
DOI: 10.1007/s11103-011-9822-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic modification of plant cell walls by expression of microbial hydrolases in the apoplast

Abstract: The systematic creation of defined cell wall modifications in the model plant Arabidopsis thaliana by expression of microbial hydrolases with known specific activities is a promising approach to examine the impacts of cell wall composition and structure on both plant fitness and cell wall recalcitrance. Moreover, this approach allows the direct evaluation in living plants of hydrolase specificity, which can differ from in vitro specificity. To express genes encoding microbial hydrolases in A. thaliana, and tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 49 publications
3
72
0
Order By: Relevance
“…Earlier, we reported the preparation of Arabidopsis plants expressing AnAXE and demonstrated that a signal peptide fused to the N terminus of the hydrolase ensures its delivery to the apoplast, and a fluorescent protein fused to the C terminus of the hydrolase does not affect its activity (Pogorelko et al, 2011). In this study, we constructed new versatile transformation vectors and expressed AnAXE and AnRAE esterases in the apoplast of Arabidopsis and Brachypodium plants characterized by type I and type II cell walls, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Earlier, we reported the preparation of Arabidopsis plants expressing AnAXE and demonstrated that a signal peptide fused to the N terminus of the hydrolase ensures its delivery to the apoplast, and a fluorescent protein fused to the C terminus of the hydrolase does not affect its activity (Pogorelko et al, 2011). In this study, we constructed new versatile transformation vectors and expressed AnAXE and AnRAE esterases in the apoplast of Arabidopsis and Brachypodium plants characterized by type I and type II cell walls, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Apoplastic fluids from aerial plant parts were extracted as described previously (Pogorelko et al, 2011). Immunoblot analyses were performed according to Magi and Liberatori (2005).…”
Section: Apoplastic Fluid Preparation and Western-blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…"y altering transcription factors in A. thaliana, it was possible both to increase cellulose and decrease lignin content [7 ] and improve secondary cell wall synthesis in ibre cells [80]. In addition, the golden pot may be near transgenic A. thaliana expressing microbial hydrolases showed no visible changes in phenotype and increased wall degradability [81]. "n alternative to decrease the transgenic debate and perhaps optimize eiciency could be altering the expression of the own plant enzymes generating a genetically modiied plant, but not a transgenic one.…”
Section: Perspectives and Targets For E G Productionmentioning
confidence: 99%
“…A CE7 AcXE gene has recently been modified by site-directed mutagenesis to create a perhydrolytic enzyme with improved activity for the production of perhydrolytic acids applicable in laundry care and disinfectant formulations [163]. AcXEs have also been employed in deacetylation of other acetylated polysaccharides [40] as well as in the post-synthetic (in planta) deacetylation of xylan to enhance lignocellulose saccharification [7,8,164,165]. In synthetic carbohydrate chemistry, AcXEs can potentially be harnessed in catalyzing regioselective transacetylation reactions [23,24,166].…”
Section: Applications Of Acxesmentioning
confidence: 99%